2003
DOI: 10.1016/s1535-6108(03)00163-6
|View full text |Cite
|
Sign up to set email alerts
|

Myeloproliferative stem cell disorders by deregulated Rap1 activation in SPA-1-deficient mice

Abstract: SPA-1 (signal-induced proliferation-associated gene-1) is a principal Rap1 GTPase-activating protein in hematopoietic progenitors. SPA-1-deficient mice developed a spectrum of myeloid disorders that resembled human chronic myelogenous leukemia (CML) in chronic phase, CML in blast crisis, and myelodysplastic syndrome as well as anemia. Preleukemic SPA-1-deficient mice revealed selective expansion of marrow pluripotential hematopoietic progenitors, which showed abnormal Rap1GTP accumulation. Overexpression of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
131
1
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(143 citation statements)
references
References 50 publications
9
131
1
2
Order By: Relevance
“…1 A). Ninety-five percent of SPA-1 Ϫ/Ϫ mice developed myeloid disorders by 16 months, with the initial signs becoming evident after 12 months (18). In the present cohort, SPA-1 Ϫ/Ϫ mice of various ages that showed no sign of the myeloid diseases by blood analysis and autopsies until 12 months and rare three 16-month-old mice without the diseases were used.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 A). Ninety-five percent of SPA-1 Ϫ/Ϫ mice developed myeloid disorders by 16 months, with the initial signs becoming evident after 12 months (18). In the present cohort, SPA-1 Ϫ/Ϫ mice of various ages that showed no sign of the myeloid diseases by blood analysis and autopsies until 12 months and rare three 16-month-old mice without the diseases were used.…”
Section: Resultsmentioning
confidence: 99%
“…E14 embryonic stem cells were transfected with a linearized SPA-1 gene-targeting vector, in which a region covering exons 5-8 was replaced by a 1.8-kb fragment containing a pgk-neo cassette, microinjected into C57BL͞6 (B6) blastocysts, and the resulting chimeras were mated with B6 mice (18). Heterozygous offspring were intercrossed to produce homozygous mutant mice, and those with mixed genetic backgrounds were used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both bone marrow preleukemic progenitors and overt leukemic blast cells in SPA-1/ mice showed markedly increased Rap1GTP levels, accompanied by a constitutive ERK activation. It was further demonstrated that the retroviral transduction of an activated mutant of Rap1, RapE63, into the normal bonemarrow progenitors significantly enhanced their expansion, whereas the overexpression of SPA-1 strongly suppressed it, confirming a positive role of Rap1 in proliferation of hematopoietic progenitors (Ishida et al, 2003). Intriguingly, in a leukemic cell line established from a SPA-1 deficient mouse with the disorder resembling CML in blast crisis, SPA-1 did not significantly affect the constitutive Erk activation and the proliferation rate, which were most likely due to constitutive activation of Ras, but abrogated the leukemogenic activity in vivo.…”
Section: Rap1 Activation By Bcr/abl and Il-3mentioning
confidence: 91%
“…Most significantly, it was found that SPA-1-deficient mice developed myeloproliferative disorders resembling CML in chronic phase and in blast crisis (Ishida et al, 2003). Both bone marrow preleukemic progenitors and overt leukemic blast cells in SPA-1/ mice showed markedly increased Rap1GTP levels, accompanied by a constitutive ERK activation.…”
Section: Rap1 Activation By Bcr/abl and Il-3mentioning
confidence: 99%